ʻAzādārī kī tārīḵẖ aur us kā is̲bāt Sunnī nuqt̤ah-yi naẓar se - Sibt̤ulḥasan, Sayyid (Muslim Salmān Mishan Pākistān, 1979)
On the history of mourning for the martyrs of Karbala, Iraq, 680, based on Sunni Muslim literature; Shia interpreatation.